Photographic Elicitation and Narration in Teachers Education and Development - Bautista García-Vera, Antonio (Teacher Education, Learning Innovation and Accountability, 2023)
This open access book discusses the functionality of the use of the language of photography in teachers' initial and ongoing training. It analyzes the nature of photography as a representation system, facilitating inquiry and reflection on its practice for teachers and evocating on theories and beliefs that may guide their work in classrooms. Photography is used to represent symbolically and affectively possible contradictions in teaching activities or the inconsistencies between planned teaching tasks and the educational purposes pursued. Resolving these conflicts is one of the ways to promote professional development. This book also describes photo-elicitation and photographic storytelling as work procedures. By analyzing the contributions of these techniques, the development of teachers is improved.